Monitoring laser weld penetration status from the optical signal - Syafiq Ahmad, Abdul Aleem; Mohd Fadhlan, Mohd Yusof; M., Ishak (IOP Publishing, 2024)
Spectrometers have demonstrated their value in laser welding by facilitating the comprehension of welding dynamics and the identification of defects. However, the complex interaction between the laser beam and the material being welded makes it difficult for spectrometers to accurately capture the depth and extent of weld penetration, predominantly because plasma formation during welding interferes. This study presents an innovative approach that integrates laser technology, spectrometers, and advanced data analysis methods to classify and characterize various penetration types in pulse laser welding procedures, with notable computational efficiency. The research entailed the execution of an experiment on a boron steel plate, wherein peak power (1000-1200 kW), pulse duration (2-4 ms), and pulse repetition rate (25-50 Hz) were systematically varied to achieve diverse penetration conditions. Two categories of joints were identified based on their depth of penetration through careful analysis of the collected data. The investigation demonstrated a positive correlation between the depth of weld penetration and the increment of laser energy, with peak power ranging from 1000 kW to 1200 kW. Consequently, an elevation in light intensity was observed related to deeper weld penetration. The information is essential for understanding the relationship between laser energy and weld penetration, highlighting the importance of controlling laser parameters to achieve desired welding results. The spectrums were analyzed using Principal Component Analysis (PCA) to distinguish between different welding conditions. Overlap was observed between data from different weld conditions due to limitations imposed by the restricted dataset. Expanding the sample size can rectify this limitation and improve the accuracy and dependability of analytical outcomes. This study's results provide valuable insights into optimizing welding parameters and improving understanding of the welding process, specifically in Tailor Weld Blanks. The findings offer potential for improving welding quality and strengthening lightweight components in high-performance industries like aerospace and automotive engineering.